A brooch from Wrocław area. A contribution to the research on the migration period in south-west Poland - Błażejewski, Artur (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2015)
In spring 2012 in the area of the village of Krzyżowice, approximately 15 km SW of Wrocław, an accidental discovery of a brooch was made. The brooch’s bow is cast in bronze, while the preserved fragments of the pin and spring were made of iron. Currently, the length of the artefact is 5 cm, but originally it was probably approximately 5.5 cm, because the base which is slightly curved upwards, was initially straight. All similar brooches come from the territory of the Thuringia tribe in the 5th/6th century AD, namely Thuringia and Bohemia. Such a dating places the brooch among the group of artefacts representing the youngest chronological horizon of the Przeworsk cultural area.